The Riviera house - Lester, Natasha, 1973- (Forever, 2021)
"Paris, 1939: The Nazis think Éliane can't understand German. They're wrong. They think she's merely cataloging the art collection in The Louvre while they steal national treasures for their private collections. They have no idea she's carefully decoding their notes to ensure every painting can be recovered after the war. But Éliane is playing a very dangerous game. Does she dare trust the man she once loved, or will he only betray her once again? She can't know for sure...until a visit to a stunning home on the Riviera dramatically changes the course of her life. Present Day: Seventy years after the end of WWII, Remy heads to a home she's mysteriously inherited on the French Riviera, wanting to forget the tragedy that has left her life in shambles and taken away those she loved most. But when she discovers a painting known to have been stolen decades ago, she begins to question everything she ever knew about her heritage. Maybe the Riviera house holds more secrets than she's ready to deal with. Or maybe, to find the answers she needs, she'll have to learn to open her heart once again"--